Al-Nahwu Al-Wazhifi Ahmad Al-Mutawakkil dan Kontribusinya pada Pengembangan Nahwu Fungsional - Abdullah, Iis Susiawati; Mardani, Dadan; Alhaq, Muhammad Faiz (IAIN Madura, 2024)
Learning nahwu in Arabic language studies is still a theme that requires the right approach so that learning Arabic for non-Arabs becomes easier and more functional. This study aims to determine the characteristics of the thinking of Ahmad al-Mutawakkil, a pioneer of functional nahwu theory, namely about al-nahwu al-wazhifi and the contribution of his thinking to the development of nahwu learning. This biographical type of literature study uses data collection techniques through reviewing and searching for library sources that are relevant to functional nahwu. Data analysis uses historical methods and content analysis. This research resulted in: 1) The characteristics of al-nahwu al-wazhifi al-Mutawakkil include: aspects of using language both spoken and written which are limited and simple, the relationship between i'rab and sentence structure is applied appropriately and correctly to produce a clear and understandable meaning, and summarizes the basic methodological principles adopted in functional grammar, 2) al-Mutawakkil's thoughts regarding al-nahwu al-wazhifi contributed greatly to the development of nahwu learning by increasing the learning outcomes of Arabic language learners. The simplification of nahwu learning which is oriented towards communication aspects prioritizes pragmatic and communicative functional elements of language.